Inflation and counter-inflationary policy measures: The case of France - Mathieu Plane; Gaston Vermersch (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
French consumer price inflation (as measured by the HICP) rose by 6.2% in September 2022 as compared to September 2021, against 10% in the euro area. Inflation rose less rapidly in France than in the euro area primarily due to a less rapid rise in energy prices: energy prices contributed to raise annual inflation by 1.9 percentage points in France as compared to 4.4 at the euro area level. Energy price inflation is lower in France partly because the economy is less reliant on gas than other euro area economies, but even more due to significant fiscal measures. The "tariff shield" on gas and electricity prices introduced at the end of 2021 and the rebate on fuel prices have strongly limited inflation. The fact remains that the French economy has been hit by a huge energy shock of the size of the first oil shock in 1974, i.e. amounting to around 3% of GDP. This energy shock is mainly absorbed by government finances, through substantial fiscal measures (3.3 percent of GDP in 2022-23), but also by employees who are suffering a record fall in real wages (-2.2% in real terms in the second quarter of 2022 as compared to a year earlier). Profit margins have remained rather stable since the last quarter of 2021 when inflationary pressure became visible, mainly because real wages cuts have offset productivity losses. In 2023, we expect nominal wages to accelerate (+3.4% in 2022 and +3.8% in 2023), which would remain below inflation (5.3% in 2022 and 5% in 2023). According to our estimates energy price inflation by itself would reduce French GDP by 1.4 percentage points in 2022 and 3.3 in 2023, but fiscal measures introduced to counter the impacts of the energy crisis will soften the economic shock by 0.8 percentage points of GDP in 2022 and 1.5 in 2023.
urn:nbn:de:101:1-2023011910431794423230
Keywords: 330; Austrian Chamber of Labour Vienna (AK Wien); Inflation; France; gas; electricity; price cap; HICP; energy; distribution; social pact; real wages